THE EFFECTIVENESS OF USING SILENT WAY METHOD WITH SPELLING GAME IN IMPROVING STUDENTS’ VOCABULARY MASTERY - Nur Auliyah; Muhammad Ihsan; Dzakiah, Dzakiah (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2023)
The objective of this research is to find out whether the use of the silent way with spelling games can improve students’ vocabulary in the eighth grade of SMPN 8 Palu or not. The knowledge of the English language in the eighth grade of SMP 8 Palu is still low, especially in vocabulary. This research aims to obtain empirical evidence about the effect of using the silent way method with spelling games. The population were all eighth-grade students of SMP 8 Palu. The sample were 44 students. The research employs a quasi-experimental design. In the experimental class, the researcher used the silent way method with a spelling game, and in the control class, the researcher used the conventional method strategy (memorizing). The researcher used an instrument in the form of multiple choice and matching tests. The instrument was given in pre-test and post-test. The finding indicated that there was a different score of the final significant mean between the classes, the serve of the experimental class was 73,40 while the final mean of the control class was 63,6. The hypothesis test shows that significant level of 5 % t-test 4,255 > t-table 1,682 so, it can be stated that H0 (Null hypothesis) was rejected and Ha (Alternative hypothesis) was accepted. Therefore, it can be concluded that the use of the Silent Way method with the Spelling Game was effective in improving students’ vocabulary in the eighth grade at SMP 8 Palu in the academic year 2021/2022.